Christian Revelation in the Photographic Arts: Urban Warfare, Light as a Borrowed Metaphor, and Roman Bordun’s The Apartment After the Artillery Bombardment in Ukraine - Victoria Phillips (Religions)
Roman Bordun’s twenty-first century photograph The Apartment After the Artillery Bombardment. Heat resistant Ceramic Vase. Irpin [Ukraine]. June 2022 uses light to express the Christian paradox of suffering that leads to redemption and eternal life for the just. In order to imbue spiritual meaning into a photographic work, Bordun draws from Renaissance artists in his use of technique (chiaroscuro), topic (warfare), and geography (the city) that all reference Christ’s Resurrection. Comparing and contrasting Bordun’s Apartment with Raffaello Sanzio da Urbino’s [Raphael] paint on wood Saint Michael Overwhelming the Demon (c. 1505) demonstrates how Bordun’s photograph can transcend its discrete historical context, merging the factual and the mythic as described by C. S. Lewis. Through his references to Raphael and the masters, Bordun lays claim to a Christian iconography and challenges the political use of religion in waging human warfare. His works all demonstrate contemporary or even quotidian plays on Renaissance works in order to address current political issues. The art of photography and stylistic references to churches’ involvement in politics, as opposed to Christian teachings, critiques Moscow’s “post-truth” justifications of the Ukrainian invasion and war.